Sexual Assault and Trauma as Reflected in Amadu Maddyâ€™s â€œNo Past No Present No Futureâ€ (1973) and Zakes Mdaâ€™s â€œThe Madonna of Excelsiorâ€ (2002) - Abera Kassaw; Melakneh Mengistu (Lakon : Jurnal Kajian Sastra dan Budaya, 2023)
This study aims to analyze the causes of sexual violence and conduct a critical examination of the traumatic impact of sexual violence as portrayed in Amadu's novel "No Past No Present No Future" and Mda's novel "The Madonna of Excelsior" by incorporating the theories of trauma by Freud, Van der Kolk, and Greenberg as the basis for the analysis. The results of this study reveal that betrayal and negative heterosexual encounters are the causes of trauma and, ultimately, post-traumatic stress disorder (PTSD) in Amaduâ€™s novel. Based on these findings, using literary texts that specifically focus on the consequences of sexual violence to educate the public about victims' reactions to rape is highly recommended. This research also suggests that psychology researchers are expected to be able to use the implications of this study to explore further the role of literature in reducing violence, including rape, and creating healthy community life.